Inadvertent doping through nutritional supplements is a reality - Van der Merwe, PJ; Grobbelaar, E (South African journal of sports medicine, 2004)
Objective. Inadvertent doping through the use of nutritional supplements is a potentially important cause of the increase in positive drug tests involving high-profile Olympic athletes. The aim of this study was to screen over-the-counter nutritional supplements for the presence of steroid or stimulant compounds banned by the International Olympic Committee (IOC) and the World Anti-Doping Agency (WADA). Method. Thirty different nutritional supplements from 14 different manufacturers were bought at shops in Bloemfontein, South Africa and analysed for testosterone and nandrolone prohormones, various ephedrines and caffeine. Results. Eighteen (60%) of the 30 supplements contained no prohibited substances. Of the 12 (40%) positive supplements, 8 (66.7%) contained prohormones and 4 (33.3%) contained stimulants. Six supplements contained prohormones, which were listed on the labels, while 2 contained prohormones not listed on the labels. The stimulants were listed on the labels as Ma Huang, Guarana and Kola extracts and all contained a mixture of ephedrines and caffeine. Conclusion. The results showed that approximately 7% of supplements tested may be mislabelled or contaminated with banned substances and that inadvertent doping through nutritional supplement use is a reality for athletes. The sporting community should therefore be aware that supplements might contain anabolic androgenic steroids and stimulants that are not declared on the labels. SA Sports Medicine Vol.16(2) 2004: 3-7